Organic–Inorganic Heterojunctions toward High‐Performance Ambipolar Field‐Effect Transistor Applications. (28th June 2018) - Li, Molin; Wang, Jiawei; Cai, Xiaoyong; Liu, Fengjing; Li, Xiaojun; Wang, Liang; Liao, Lei; Jiang, Chao
Abstract: This work reports on combination of organic–inorganic heterojunctions between amorphous indium–gallium–zinc oxide (a‐IGZO) and organic semiconductors for design of high‐performance ambipolar transistors. A vertically sequential layer device configuration that the organic small molecule dinaphtho‐thieno‐thiophene (DNTT) and dioctylbenzothieno[2, 3‐ b ]benzothiophene (C8‐BTBT) are directly vacuum deposited on the surface of a‐IGZO without any interface modification is employed in ambipolar transistors. The ambipolar transistors based on C8‐BTBT/a‐IGZO featured with V‐shaped transfer curves exhibit an outstanding electrical performance with mobilities as high as 5.1 and 4.5 cm 2 V −1 s −1 for electrons and holes, respectively. The formation of N‐type channel even if covered with several tens of nanometers thick small molecule film is clarified with the charge injection mechanisms based on both thermionic injection and/or tunneling transport processes. High‐performance ambipolar inverter with extremely large gain of 124 V/V is fabricated based on the C8‐BTBT/a‐IGZO ambipolar transistors. Moreover, a single‐transistor frequency doubler shows high spectral purity with 70% of the output energy at the doubling frequency of 2 kHz. The present work provides a strategy for manufacturing high‐performance ambipolar transistor with straightforward processing approaches, which may help deepen the understanding of ambipolar channel's working mechanisms and optimize the design procedures of logic electrical components. Abstract : A vertically sequential layer device configuration that the organic molecule dinaphtho‐thieno‐thiophene and dioctylbenzothieno[2, 3‐ b ]benzothiophene (C8‐BTBT) are directly vacuum deposited on the surface of amorphous indium–gallium–zinc oxide (a‐IGZO) is employed in ambipolar transistors. The ambipolar transistors based on C8‐BTBT/a‐IGZO featured with V‐shaped transfer curves exhibit an outstanding electrical performance with mobilities as high as 5.1 and 4.5 cm 2 V −1 s −1 for electrons and holes.